Mediation as an alternative dispute resolution: world experience - I. Korobko, Kseniya (2019)
The present paper is devoted to the application of mediation as an alternative dispute resolution procedure. It defines features of the legal regulation of mediation procedures in different countries and legal systems, such as United States, European Union, China, and Russian Federation. In addition, the main principles of mediation and their implementation in different legal systems are analyzed in this paper. Furthermore, the reasons for the emergence of this institution in these countries are determined and the circumstances hindering development of mediation have been identified. Moreover, conclusions concerning the degree of development of alternative dispute resolution have been formulated.